Endoscopic therapy through dilatation of benign esophageal stenosis - Elizabeth Montes de Oca Megías; Guillermo Noa Pedroso; Mildred Cecilia Armenteros Torres; Andria de la Cruz de Oña; Enrique Olazabal García; Norberto Alfonso Contino (Universidad de Ciencias Médicas de La Habana, 2018)
Introduction: Endoscopic dilatation is the first therapeutic option to eliminate benign esophageal stenosis and improve the symptoms and the quality of life of those patients who suffer from it. Objective: To describe the results of endoscopic dilatation in patients with benign esophageal stenosis treated in the National Center for Endoscopic Surgery from January 2015 to December 2016.  Material and Methods:A case series longitudinal observational study was conducted in 59 patients with benign esophageal stenosis. Dilatations were done with Savary-Gilliard bougie and balloons. Results: The mean age was 52,5 years, and the condition predominated in 37 male patients (62,7%). Post-surgical, peptic, and caustic were the most frequent etiologies with 25, 14, and 6 cases, respectively.  Short stenosis predominated in 51 cases. Bougies were used in 48 patients for a total of 149 dilatations, corresponding to a mean of 3,1 dilatations/ patients. Correction of the stenosis was made in 1-3 sessions in 47 % of patients; 11 cases were dilated with balloon, corresponding to a mean of 1- 3 dilatations/ patients. Four patients from the group that were dilated with Savary-Gilliard bougies showed refractoriness. A perforation, and two bleedings occurred.  After the dilatations, dysphagia improved or disappeared in 93,2 % of patients. Conclusions: Endoscopic therapy through dilatation of benign esophageal stenosis indicated to be a good alternative method in achieving corrections in a few dilatation sessions, with a low number of complications, and an improvement of the dysphagia.   Keywords: esophageal stenosis, benign esophageal stenosis, endoscopic therapy, balloon dilatation, dilatation with Savary-Gilliard bougies.